Sistem Pengelolaan Alat Bengkel Berbasis Data Matrix untuk Efisiensi Operational - Wiguna, Fendy Arjun; Rodianto, Rodianto (JATISI, 2025)
This study aims to design and implement a Workshop Equipment Management System based on Data Matrix technology to enhance operational efficiency. The system utilizes Data Matrix technology, which features high storage capacity, error correction capability, and durability in harsh working conditions. Developed using the Waterfall model, the system supports real-time recording, tracking, and maintenance of tools. Implementation in Aneka Usaha Workshop, Sumbawa Regency, demonstrated improved operational efficiency, reducing tool recording time from an average of 15 minutes to 3 minutes, with a Barcode reading accuracy of 98%. Key features such as automated maintenance reminders, digital inventory integration, and tool labeling with water- and scratch-resistant Barcodes enable more structured and reliable management. Testing results confirm the system meets functional and non-functional specifications, delivering fast response times and low failure rates. The system can be further developed by integrating AI-based analytics for maintenance prediction and applied in other sectors such as manufacturing and logistics. Additionally, technical training for employees and infrastructure upgrades, such as high-resolution cameras, are recommended to enhance system performance.